KAJIAN PENGARUH RISE-SPAN RATIO PADA JEMBATAN TIED ARCH - Eko Felix Songbes; Made Suangga; Sunarjo Leman (JMTS: Jurnal Mitra Teknik Sipil, 2023)
The economic growth of a region in Indonesia is strongly influenced by road and bridge infrastructure. The problem is to design the optimal configuration of the rise-span ratio of the tied arch bridge. This problem must be studied further due to the maximum load combination according to SNI 1725:2016 and SNI 2833:2016. This study aims to understand the effect of rise-span ratio on deformation, natural frequency, magnitude of seismic forces, internal forces and optimum rise-span ratio on a tied arch bridge. This is based on previous research that neglecting the rise-span ratio affects the behavior of the structure as a whole, this needs to be studied according to the location where the bridge is built, because there is an influence from the seismic force response spectrum. The loading given is in accordance with SNI 1725:2016 and SNI 2833:2016. Modeling and structural analysis using Midas Civil software. The rise-span ratio (f/L) used is 1:10.00, 1:8.00, 1:5.71, 1:4.44, 1:3.64, 1:3.07, 1:2.67, 1:2.35, 1:2.09, 1:2.00, the length (L) of the tied arch bridge is 60 meters. The effect of the rise-span ratio on deformation is directly proportional, while the compressive axial force on the acrh rib is inversely proportional. Abstrak Pertumbuhan ekonomi suatu daerah di Indonesia sangat dipengaruhi oleh infrastruktur jalan dan jembatan. Adapun permasalahannya adalah merancang konfigurasi rise-span ratio jembatan tied arch optimum. Permasalahan ini harus dikaji lebih lanjut akibat kombinasi beban maksimum sesuai SNI 1725:2016 dan SNI 2833:2016. Studi ini bertujuan untuk memahami pengaruh rise-span ratio terhadap deformasi, frekuensi alami, besarnya gaya gempa, gaya-gaya dalam dan rise-span ratio optimum pada jembatan tied arch. Hal ini didasari pada penelitian terdahulu bahwa pengabaian rise-span ratio berpengaruh pada perilaku struktur secara keseluruhan, ini perlu dikaji sesuai dengan letak jembatan tersebut dibangun, karena ada pengaruh dari gaya gempa respons spektrum . Pembebanan yang diberikan sesuai dengan SNI 1725:2016 dan SNI 2833:2016. Pemodelan dan analisis struktur menggunakan software Midas Civil. Rise-span ratio (f/L) digunakan adalah 1:10,00, 1:8,00, 1:5,71, 1:4,44, 1:3,64, 1:3,07, 1:2,67, 1:2,35, 1:2,09, 1:2,00, panjang (L) jembatan tied arch adalah 60 meter. Pengaruh rise-span ratio terhadap deformasi adalah  berbanding lurus, sedangkan gaya aksial tekan pada acrh rib adalah berbanding terbalik.